CCAFS East Africa Hoima, Uganda Site Visit - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
A site visit to Hoima, Uganda one of the CCAFS East Africa sites, showcasing some of the climate information services and farmer training activities. Photo J. Recha (CCAFS)